Kepuasan dan Kepercayaan Pelanggan serta Loyalitas Pengguna Belanja Online Selama Pandemi COVID-19 - Besse Faradiba (Jayapangus Press, 2021)
The purpose of this research is to analyze the correlation between satisfaction, trust, and loyalty of online shopping users in the midst of COVID-19 Pandemic. This research was conducted at Parepare of South Sulawesi. The sample of this research was fifty people having the hobby with online shopping. Data were analyzed using correlation test. The result of this research found that there are strong positive correlations between customers satisfaction, trust, and loyalty amidst of pandemic. It reveals that the increase of satisfaction and trust relates to the loyalty of online shopping users.